THE MANIFESTATION OF DIALECTICAL PRINCIPLES IN THE LIFE OF THE HUMAN AND SOCIETY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the meaning of human life and the nature of social relationships. It is well known that the purpose of the human being, who enters social relations as an intelligent creature, changes dramatically. The former surfing is replaced by a dark way of life, focused on a particular purpose. Humans begin to realize themselves, to understand the mystery of the world around them. The article analyzes how social relations coincide with the time human beings  began to act as intelligent beings, the human being as a conscious being, developing conscious relationships with other people, and developing social relationships in the first place to conclude. The topic in this article is analyzed from the perspective of the modern era, based on the philosophers of the ancient period, such as Plato and Aristotle.